Development of a Quantitative Real-Time PCR Assay for Detection of Toxoplasma gondii in Brain Samples - Mahboubeh Berizi (Tehran University of Medical Sciences, 2021)
Background: Toxoplasmosis is a worldwide-distributed infection that can cause serious diseases, mainly in congenitally infected and immunodeficient individuals. PCR assays play an indispensable role in the detection of Toxoplasma gondii in different biological samples.